Differences in L-alanine uptake by livers of Wistar and lean Zucker rats. Issue 2 (April 1991) - Ruiz, B.; Casado, J.; Pastor-Anglada, M.; Felipe, A.
Abstract : The L-alanine uptake by livers of Wistar and lean Zucker rats has been studied. The hepatic uptake and fractional extraction rates of alanine were estimated in 50–55 day old rats. No significant differences in amino acid concentrations and blood flows in afferent and efferent liver vessels were seen in lean Zucker rats when compared with Wistar rats. However, the hepatic uptake (1.6±0.1 and 0.7±0.1 μmol/min/100 g bw, p<0.01) and the fractional extraction (26.8±2.1 and 15.2±3.1%, p<0.05) were much lower in Zucker than in Wistar rats. The hepatic active transport of L-alanine was determined in vitro using isolated plasma membrane vesicles. Vesicles isolated from livers of lean Zucker rats showed similar values of Km (2.5±0.7 vs 2.0±0.5 mM for Wistar and Zucker respectively, N.S.), but lower values of Vmax when compared with Wistar rats (1.1±0.1 vs 0.6±0.005 nmol/mg prot 5 s, p<0.01, for Wistar and lean Zucker rats respectively). These results indicate that, the liver of lean Zucker rats concentrates alanine less efficiently than the liver of Wistar rats. This fact correlates well with a lower capacity of the Na + -dependent L-alanine trasport in liver plasma membrane vesicles from lean Zucker rats.